Alternative sources of oils and fats from Amazonian plants: Fatty acids, methyl tocols, total carotenoids and chemical composition. (February 2019) - Serra, Josilene Lima; Rodrigues, Antônio Manoel da Cruz; de Freitas, Rilton Alves; Meirelles, Antonio José de Almeida; Darnet, Silvain Henri; Silva, Luiza Helena Meller da
Abstract: Amazonian plants possess high amounts of little-explored lipid compounds. Chemical parameters and lipophilic compounds present in twelve oils and fats from different Amazonian plants were characterized. The fatty acids identified reveal saturated fats, such as babassu oil and muru-muru fat (rich in lauric acid), ucuhuba fat (myristic acid), and bacuri fat (palmitic acid). Buriti, pracaxi, and patawa oils showed high oleic acid content. Passion fruit seed and Brazil nut oils had high levels of the polyunsaturated fatty acids rich in linoleic acid. The oleaginous plants had high unsaturation degree and high content of medium-length-chain fatty acids due to high values of iodine, saponification, and peroxide. For methyl tocols and total carotenes, a simultaneous determination method was used and revealed high levels of these vitamins in buriti oil. No previous work in the literature has described all these parameters in Amazonian oils and fats, especially regarding plant species such as bacuri, cupuassu, and ucuhuba. These results provide information on oils and fats that could be used as alternative sources of raw material for the food and pharmaceutics industries. Graphical abstract: Unlabelled Image Highlights: Amazonian oils and fats are rich in polyunsaturated and highly saturated fatty acids. Myristic acid is found in ucuhuba fat and few oleaginous plant sources are known to produce it. Buriti oil had the highest methyl tocol and vitamin A contents with antioxidant potential. Amazonian plants are an alternative of raw material for industrial application.